The macroeconomic environment of business core concepts and curious connections - Levi, Maurice D. 1945- (Singapore World Scientific, 2014)
This book provides an introduction to principal macroeconomic phenomena: inflation, unemployment, national income, interest rates and exchange rates. It describes how each phenomenon is measured, what makes it change and the consequences of change. The goal is to provide a degree of literacy about the economy which constitutes the environment of business.
A word to the instructor -- A word to the student -- Acknowledgements -- National income and product account : connections: accounting for national economic performance -- National debt : connections: natural economy -- Money, banking, and financial intermediation : connections: money- a matter of considerable interest -- Inflation : connections: economics doesn't exist in a vacuum -- Unemployment : connections: physical and human dimensions of redundancy -- Economic fluctuations and growth : connections: balancing acts and perpetual motion -- Interest rates : connections: a long history of interest -- Exchange rates : connections: precious parallel.
Includes bibliographical references and index.
Keywords: Macroeconomics